2021
DOI: 10.1038/s41598-021-82113-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of surface-enhanced Raman spectroscopic fingerprints of kidney transplant recipient urine with kidney function parameters

Abstract: Routine monitoring of kidney transplant function is required for the standard care in post-transplantation management, including frequent measurements of serum creatinine with or without kidney biopsy. However, the invasiveness of these methods with potential for clinically significant complications makes them less than ideal. The objective of this study was to develop a non-invasive tool to monitor the kidney transplant function by using Surface-Enhanced Raman Spectroscopy (SERS). Urine and blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…Thus, the spectral bands and SERS characteristics of the serum obtained in the current study are similar to those reported in the studies of other authors. However, Huang et al and Feng et al [35,36] reported SERS bands at 702 cm -1 and 1383 cm -1 which were not observed in our study; these bands were assigned to the cytosine and CH3 domains respectively.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…Thus, the spectral bands and SERS characteristics of the serum obtained in the current study are similar to those reported in the studies of other authors. However, Huang et al and Feng et al [35,36] reported SERS bands at 702 cm -1 and 1383 cm -1 which were not observed in our study; these bands were assigned to the cytosine and CH3 domains respectively.…”
Section: Resultscontrasting
confidence: 88%
“…Silicon substrates were immersed in an Ag NP colloidal solution to allow Ag NPs to adhere to the surface. Huang et al and Zong et al [35,61] prepared colloids by adding NaOH solution to hydroxylamine hydrochloride solution and mixing the solution with AgNO3 aqueous solution at room temperature, until the formation of a milky-grey color. The Ag colloids were pelleted by centrifugation.…”
Section: Resultsmentioning
confidence: 99%
“…Second, SERS can distinguish multiple substances at the same time. Third, SERS may be a more convenient, less expensive, and faster tool than traditional techniques in clinical and biochemical laboratories [ 11 ]. On the other hand, the SERS technique has limitations in that (1) it requires intimate contact between the enhancing surface and the analyte, (2) the substrates degrade over time, resulting in a decrease in signal, (3) the substrates have limited selectivity for a given analyte, (4) the substrates have limited reusability, and (5) there are problems with homogeneity and reproducibility of the SERS signal within a substrate [ 12 ].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Research in the last decades has published several methods based on RS and SERS for the detection of urinary renal biomarkers, including urea peaks at 1004 cm −1 (symmetrical CN stretch) and 1161 cm −1 (attributed to NH 2 modes), creatinine peaks at 608 cm −1 (NCH 3 stretching, CO deformation and ring vibrations), 680 cm −1 (CNH 2 and CO stretching, ring vibrations), 846 cm −1 (CNH 2 deformation and ring vibrations), and 910 cm −1 (C–C–N stretching), glucose peak at 1128 cm −1 (C–O stretching), and protein peaks at 600, 850, 1060, and 1470 cm −1 (disulfide bonds, tyrosine, C–N bonds, and CH 2 and CH 3 angle bending) [ 23 , 24 , 25 , 26 ]. An overview of the most important findings of these studies is presented in Table 1 [ 11 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The applications of RS for the identification of uropathogens, urine crystals, and kidney stones are not included in this review.…”
Section: Raman Spectroscopy: a Novel Tool To Detect Renal Biomarkers?mentioning
confidence: 99%
See 1 more Smart Citation